2013
DOI: 10.3390/ijms140714119
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Gamma-H2AX Assay for Radiation Biodosimetry in a Swine Model

Abstract: There is a paucity of large animal models to study both the extent and the health risk of ionizing radiation exposure in humans. One promising candidate for such a model is the minipig. Here, we evaluate the minipig for its potential in γ-H2AX-based biodosimetry after exposure to ionizing radiation using both Cs137 and Co60 sources. γ-H2AX foci were enumerated in blood lymphocytes and normal fibroblasts of human and porcine origin after ex vivo γ-ray irradiation. DNA double-strand break repair kinetics in mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 58 publications
(66 reference statements)
8
33
0
Order By: Relevance
“…The average radiation induced gH2AX foci number per epidermal keratinocyte then declined after 70 days; however, the average numbers of residual gH2AX foci per epidermal keratinocyte at 70 days were significantly higher compared to non-irradiated controls [118]. Twenty-four hours after ex vivo exposure to 1.8 Gy of IR, both human and minipig lymphocytes exhibited $15% of the maximal gH2AX response observed at 30 min [33]. Furthermore, approximately 3% residual gH2AX foci were found in human and minipig fibroblasts for up to 24 h after 2 Gy of IR exposure.…”
Section: Minipig Skin Lymphocytes and Fibroblastsmentioning
confidence: 87%
See 2 more Smart Citations
“…The average radiation induced gH2AX foci number per epidermal keratinocyte then declined after 70 days; however, the average numbers of residual gH2AX foci per epidermal keratinocyte at 70 days were significantly higher compared to non-irradiated controls [118]. Twenty-four hours after ex vivo exposure to 1.8 Gy of IR, both human and minipig lymphocytes exhibited $15% of the maximal gH2AX response observed at 30 min [33]. Furthermore, approximately 3% residual gH2AX foci were found in human and minipig fibroblasts for up to 24 h after 2 Gy of IR exposure.…”
Section: Minipig Skin Lymphocytes and Fibroblastsmentioning
confidence: 87%
“…Furthermore, approximately 3% residual gH2AX foci were found in human and minipig fibroblasts for up to 24 h after 2 Gy of IR exposure. gH2AX kinetics in minipig lymphocytes after exposure to different total body irradiation doses showed that persistent gH2AX foci per cell were proportional to the initial IR dose thus suggesting that a portion of IR-induced DSBs remains unrepaired [33].…”
Section: Minipig Skin Lymphocytes and Fibroblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…This sensitivity allows detection of RT-induced DNA damage in situ in human tissues, such as peripheral blood lymphocytes (PBL) and hair follicles (10). The application of this assay in the case of homogeneous total body irradiation is straightforward and relies on the measurement of the average number of γ-H2AX foci per cell (11,12). However, a robust relationship between partial body irradiation dose/volume and resultant DNA DSBs are yet to be established.…”
Section: Introductionmentioning
confidence: 98%
“…The cause of the sensitivity of minipig to acute radiation in terms of relatively low LD50 compared to other species [17] has not been established. In the adult Göttingen minipig, sensitivity was not associated to abnormal response of the bone marrow or the gastrointestinal system [6,7], nor to defects in the DNA repair ability [18], but it appeared to be linked to the extent of systemic inflammation triggered by radiation damage [9]. Features in hormonal status of the Göttingen minipig may contribute to the sensitivity of this strain to irradiation.…”
Section: Discussionmentioning
confidence: 99%